Obesity Contributes to Cardiac Autonomic Dysfunction in Prehypertensives - Rafiq, Nadeema; Nabi, Tauseef; Charak, Garima (Journal of Neonatal Surgery, 2025)
Background & Objectives: A simple non-invasive method for evaluating the extent of heart rate variation caused by the cardiac autonomic nervous system (ANS) is heart rate variability (HRV). The study's objective was to evaluate the effects of isometric handgrip exercise (IHG) on HRV in pre-hypertensive obese and non-obese subjects. Materials & Methods: 180 healthy young adults between the ages of 18 and 30 took part in this observational study. Subjects in group I had a “Body Mass Index” (BMI) <25 and were normotensive; those in group II had a BMI <25 and were pre-hypertensive; and those in group III had a BMI >25 and were pre-hypertensive. Groups I, II, and III each included sixty members. “Low-Frequency Power” (LF), “High-Frequency Power” (HF), and the LF/HF ratio had been computed as part of the HRV study (Chart HRV module, AD Instruments Pty Ltd). Results: It was found that pre-hypertensive individuals had a considerably higher LF/HF ratio than controls. In comparison to pre-hypertensive participants with a BMI < 25, those with a BMI >25 exhibited significantly higher values of the LF/HF ratio. The current research demonstrated a correlation between the LF/HF ratio and both hypertension (HTN) and BMI. Conclusion: The dysfunction of the cardiac ANS, particularly with regard to sympathetic activity, was examined by HRV measures in obese pre-hypertensive patients. Our results provide evidence that autonomic dysfunction occurs in the early stages of HTN.